(untitled) (Colloquia Comparativa Litterarum, 2021)
The Strange Knight of the Sacred Book is a novel by Anton Dontchev, a Bulgarian author, published in 1998 in Bulgaria and translated in France in 1999. It tells how, around 1218-1219, the secret Book of the Bulgarian Bogomils arrived in France to their Albigensian brothers, in Languedoc, in Occitan country. It is inspired by numerous readings of epic and courtly literature of the thirteenth century, in Latin and French, in the languages of oc and oïl, and more recent, historical and literary sources, of the nineteenth and twentieth centuries. There are also references to medieval tapestries, to 15th century religious paintings, Italian, Spanish or Portuguese, and to modern, English and French painters of the 19th and 20th centuries. It is a singular, Bulgarian look, rare in modern literature, and devoted to the history of the crusade carried out at the beginning of the 13th century, in Occitania, against the Albigensians. It is a long solitary, pseudo-autobiographical reverie, a long return to oneself nourished by past adventures, intimate thoughts and moral and spiritual reflections of the narrator: a French knight, at first a crusader, later a rebel against the papacy and the Inquisition.